1966
DOI: 10.1039/j39660000106
|View full text |Cite
|
Sign up to set email alerts
|

Organomercury compounds. Part I. Mercury pentafluorobenzoates and their decarboxylation to pentafluorophenylmercury compounds

Abstract: The preparations of some mercury derivatives of pentafluorobenzoic acid and their decarboxylation to give pentafluorophenylmercury compounds are described. Mercuric pentafluorobenzoate and C,F,CO,HgR ( R = Ph, p-MeCGH4, or p-MeOC,H,) have been prepared by reaction of pentafluorobenzoic acid with mercuric acetate and R HgOAc, respectively, and methylmercuric pentafluorobenzoate has been made from methylmercuric iodide and silver pentafluorobenzoate. The complexes (C6F5C0,)zHgL ( L = 2,2'-bipyridyl, 1 ,I O-phena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…A similar equilibrium had been observed by Sheppard when studying the carboxyl displacement from [Cu(OAc)] to [Cu(O 2 CR)] (R=C 6 F 5 , o ‐NO 2 C 6 H 4 , CClF 2 and CCF 3 ) 10. In contrast, the RC(O)OHg bond was found to be resistant to AcOH 15. Interestingly, repeating the reaction using 2‐nitrobenzoic acid ( 2 b ) with 1 a led to 90 % conversion to the corresponding gold(I) 2‐nitrobenzoate intermediate ( 4 b ).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…A similar equilibrium had been observed by Sheppard when studying the carboxyl displacement from [Cu(OAc)] to [Cu(O 2 CR)] (R=C 6 F 5 , o ‐NO 2 C 6 H 4 , CClF 2 and CCF 3 ) 10. In contrast, the RC(O)OHg bond was found to be resistant to AcOH 15. Interestingly, repeating the reaction using 2‐nitrobenzoic acid ( 2 b ) with 1 a led to 90 % conversion to the corresponding gold(I) 2‐nitrobenzoate intermediate ( 4 b ).…”
Section: Resultssupporting
confidence: 76%
“…[10] In contrast, the RC(O)OÀHg bond was found to be resistant to AcOH. [15] Interestingly, repeating the reaction using 2-nitrobenzoic acid (2 b) with 1 a led to 90 % conversion to the corresponding gold(I) 2-nitrobenzoate intermediate (4 b). Ultimately, these data suggested that the displacement of the equilibrium is likely pK a -dependent with respect to the benzoic acid employed.…”
Section: Resultsmentioning
confidence: 99%
“…1680 cm −1 is characteristic of an asymmetric O−C−O stretching mode of a monodentate ligand. Variable denticities of carboxylate ligands to different metallic centers have been previously reported; 15,66 uranyl complexes having variable denticity have been reported by Groenewold and collaborators. 67 The peak at ca.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Decarboxylation reactions of condensed-phase metal carboxylates is a well-established method of synthesis of organometallic compounds. Deacon and collaborators have synthesized and studied the structural and vibrational properties of uranyl pentafluorobenzoate and its coordination derivatives with 2,2′-bipyridyl, triphenylphosphine oxide, and triphenylarsine oxide. This report includes thermal decomposition studies of the same solution complexes, which however do not yield UO 2 (C 6 F 5 ) 2 derivatives by decarboxylation …”
Section: Introductionmentioning
confidence: 99%
“…Unsymmetrical phenylpentafluorophenyl and methylpentafluorophenyl compounds are obtained from the appropriate mercury(II) halide [45], or by decarboxylation procedures [69], and these mixed derivatives are particularly susceptible to attack. Unsymmetrical phenylpentafluorophenyl and methylpentafluorophenyl compounds are obtained from the appropriate mercury(II) halide [45], or by decarboxylation procedures [69], and these mixed derivatives are particularly susceptible to attack.…”
Section: Cleavage By Electrophilesmentioning
confidence: 99%